(untitled) (Journal of the College of Basic Education, 2025)
The aim of the research is to (reveal the toxicological features of the rapidly perceived image in the pupils of the sixth grade of primary school?). To achieve it, I followed the descriptive and analytical approach, using an analysis form consisting of (11) traits that obtained apparent honesty after presenting it to a group of experts, as I indicated a high stability rate by analyzing (10) drawings, and the research community consisted of (157) images in the book of science of the sixth grade primary and with a sample of (15) images.After applying the analysis form consisting of (11) attributes and on a triple scale, the researcher used in the analysis of its data the statistical bag to extract the results, which indicated a clear weakness in the appearance of the toxicological features of the image. Which leads to a delay in its perception in pupils, and through the results of the research, the researcher concluded that there is a direct relationship between the toxicological features of the image in terms of its appearance, being subject to accurate scientific laws and standards. The researcher also recommended the design of images accompanying the scientific content according to the current research analysis form.